Pediatric oncology social workers' experience of compassion fatigue. Issue 6 (2nd November 2018) - Yi, Jaehee; Kim, Jonghee; Akter, Jesmin; Molloy, Jennifer K.; Ah Kim, Min; Frazier, Kristin
Abstract: Pediatric oncology social workers play an important role in supporting cancer patients and their families as they learn to talk about and cope with the physical and psychological impacts of cancer. As a result, social workers are particularly vulnerable to compassion fatigue and the associated psychological and physical impacts. The purpose of this qualitative study was to understand the experience of compassion fatigue among 27 pediatric oncology social workers. Four main themes emerged throughout the five focus groups: Conditions that contribute to compassion fatigue; the influence of compassion fatigue; coping strategies to alleviate compassion fatigue; and desire for systematic support to prevent compassion fatigue. Our study findings emphasize the importance of developing programs, policies and research geared toward the prevention of compassion fatigue, in addition to coping with symptoms. Further, this study brings attention to the importance of including pediatric oncology social workers in efforts to develop and implement systemic supports.